Social protection expenditure on health in later life in 20 European countries: Spending more to reduce health inequalities. (January 2022) - Sieber, Stefan; Orsholits, Dan; Cheval, Boris; Ihle, Andreas; Kelly-Irving, Michelle; Delpierre, Cyrille; Burton-Jeangros, Claudine; Cullati, Stéphane
Abstract: Background: This study aims to examine whether higher social protection expenditure reduces the negative association of life-course socioeconomic disadvantages with subjective and objective health status and trajectories in later life. Methods: We used SHARE data from participants living in 20 European countries aged 50 to 96. Seven waves allowed to examine the trajectories of health inequalities in later life. We used linear mixed-effects models stratified by sex to examine the association between life-course socioeconomic disadvantage and subjective (self-rated health, SRH, N = 55, 443) and objective (grip strength, N = 54, 718) health. Cross-level interactions between net social protection expenditure as percentage of gross domestic product and life-course socioeconomic disadvantage tested for the moderating effect of social expenditures on the association of disadvantage with SRH and grip strength in later life. Findings: Higher social protection expenditure reduced socioeconomic health inequalities in both men and women for grip strength, and in women but not men for SRH. For SRH, the health-inequality-reducing effect of social protection expenditure became weaker with increasing age. This was not observed in grip strength. Some separate expenditure functions (disability, family and children) were found to have inequality-widening effects in men's and women's SRH, which were either offset or overcompensated by the other functions. No inequality-widening effects were observed in grip strength. Interpretation: Higher social spending reduces life-course socioeconomic inequalities in women's subjective health and in men's and women's objective health. However, some specific social protection policies may have the unintentional effect of increasing inequalities in people's evaluation of their own health. Highlights: Life-course socioeconomic disadvantage associated with poor health in old age. The longer the exposure, the worse subjective and objective health. Spending in social protection reduces inequalities in women's subjective health. Spending in social protection reduces inequalities in both sexes' objective health. Some specific social protection policies increase inequalities in subjective health.